Experience of the Time to Change programme in England as predictor of mental health service users' stigma coping strategies. (28th July 2016) - Sampogna, G.; Bakolis, I.; Robinson, E.; Corker, E.; Pinfold, V.; Thornicroft, G.; Henderson, C.
Abstract : Aims: In the field of stigma research, an area of interest is the coping strategies that mental health service users can use in response to discriminatory experiences. As a part of the evaluation of the Time to Change (TTC) anti-stigma programme, the Viewpoint telephone survey was run annually in order to assess service users' reported levels of discrimination and selected coping strategies. The study aim is to test the extent to which experience of TTC programme is a positive predictor of selected coping strategies. Methods: Telephone interview surveys carried out by peer interviewers were conducted annually. 'Educating others' and 'challenging' coping strategies were assessed alongside anticipated and experienced discrimination. Results: During 2011–2014, 3903 mental health service users were interviewed. Participants more often adopted the 'educating others' strategy (2.31 ± 0.01) than the 'challenging' strategy (2.15 ± 0.02) ( p < 0.001). On the other hand, those who participated in campaign activities endorsed 'challenging' more frequently than people who were not aware of TTC (2.78 ± 1.23 v. 2.09 ± 1.08, p < 0.001). According to the multi-variate linear regression model, we found that being actively involved in TTC activities (OR = 0.74, CI: 0.29–1.19; p < 0.05), having a diagnosis of a depressive disorder (OR = 0.20, CI: 0.04–0.36; p < 0.05) or personality disorder (OR = 0.23, CI: 0.04–0.43; p < 0.05) were good predictors of endorsing a 'challenging' strategy even after adjusted for confounding variables. Conclusions: A positive relationship between participating in the TTC programme and using the 'challenging' strategy was found. There is still a need to disentangle the complex association between these two coping strategies and the role of anti-stigma campaigns, promoting further local activities led by service users and carers' as well as all others stakeholders' associations.